1993
DOI: 10.1107/s0108270192013064
|View full text |Cite
|
Sign up to set email alerts
|

Structure of lithium nickel phosphate

Abstract: Experimental. LiNiPO4 was prepared as a polycrystalline powder by solid-state reaction between Li2CO3, NiO and NH4H2PO4. Stoichiometric quantities of the starting materials were ground together in an agate mortar and pestle for 15 min. After drying, the resulting mixture was placed in a gold boat. The sample was heated in a muffle furnace at 573 K for 2 h and then at 923 K for another 2h to decompose the phosphate and carbonate, respectively. This was followed by 36 h at 1023 K with one intermediate regrinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 4 publications
3
39
0
1
Order By: Relevance
“…23 All members of this family were found to be antiferromagnets with the same magnetic structure differing only in the spin direction; [24][25][26] however, a recent single-crystal study of LiNiPO 4 revealed that the magnetic spins are not collinear in the AFM ground state but are slightly canted within the ac plane. 27 Neutron-scattering studies demonstrated that LiMPO 4 ͑M = Ni, Co, and Mn͒ exhibit properties between two dimensions ͑2D͒ and three dimensions ͑3D͒ with an interlayer coupling that is stronger relative to the coupling found in the cuprates, for instance.…”
Section: -0121/2009/79͑17͒/174435͑7͒mentioning
confidence: 99%
“…23 All members of this family were found to be antiferromagnets with the same magnetic structure differing only in the spin direction; [24][25][26] however, a recent single-crystal study of LiNiPO 4 revealed that the magnetic spins are not collinear in the AFM ground state but are slightly canted within the ac plane. 27 Neutron-scattering studies demonstrated that LiMPO 4 ͑M = Ni, Co, and Mn͒ exhibit properties between two dimensions ͑2D͒ and three dimensions ͑3D͒ with an interlayer coupling that is stronger relative to the coupling found in the cuprates, for instance.…”
Section: -0121/2009/79͑17͒/174435͑7͒mentioning
confidence: 99%
“…The lithium orthophosphates LiMPO 4 (M = = Co 2+ or Ni 2+ ) are isostructural with the minerals lithiophilite (M = Mn) and triphilite (M = Fe), which belong to the olivine family [1,11,12]. The orthorhombic unit cell contains four formula units and is described by space group Pnma (D 2h 16 ) [12].…”
Section: Structural and Magnetic Features Of Linipomentioning
confidence: 99%
“…The orthorhombic unit cell contains four formula units and is described by space group Pnma (D 2h 16 ) [12].…”
Section: Structural and Magnetic Features Of Linipomentioning
confidence: 99%
“…LiNiPO 4 is an antiferromagnetic (AF) insulator [9,10] which belongs to the olivine family of lithium orthophosphates LiMPO 4 (M = Mn, Fe, Co, and Ni) [11]; space group is Pnma [12]. Neutron scattering studies demonstrated that LiMPO 4 (M =Ni, Co) exhibit properties between the two-dimensional (2D) and three-dimensional (3D) with an interlayer coupling that is relatively stronger than the coupling found in the cuprates, for instance [13,14].…”
mentioning
confidence: 99%